2019
DOI: 10.3892/mmr.2019.10386
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA sequencing reveals the molecular mechanism of the effects of acupuncture and moxibustion on endometrial receptivity in patients undergoing infertility treatment

Abstract: The present study aimed to determine the profile of differentially expressed circular RNAs (circRNAs) in infertile patients treated with acupuncture and moxibustion and verify the role of acupuncture and moxibustion in altering endometrial receptivity (ER). High-throughput RNA sequencing and bioinformatics analysis of samples from six pairs of patients treated with or without acupuncture and moxibustion were conducted. The reliability of high-throughput RNA sequencing was validated using reverse transcription-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…Circular RNA (circRNA) is a class of single-stranded covalently closed RNA molecules that was first discovered in pathogens by Sanger et al in 1976 [1]. It is now generally accepted that circRNA is generated by a process named back-splicing [2], and increasing studies have demonstrated that circRNA plays important roles in the occurrence, development and prognosis of various diseases, including tumorigenesis [3][4][5], neurodevelopmental processes [6] autoimmune responses [7], and infertility [8]. However, studies on how circRNA is regulated before exerting specific biological functions are still limited [9].…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNA (circRNA) is a class of single-stranded covalently closed RNA molecules that was first discovered in pathogens by Sanger et al in 1976 [1]. It is now generally accepted that circRNA is generated by a process named back-splicing [2], and increasing studies have demonstrated that circRNA plays important roles in the occurrence, development and prognosis of various diseases, including tumorigenesis [3][4][5], neurodevelopmental processes [6] autoimmune responses [7], and infertility [8]. However, studies on how circRNA is regulated before exerting specific biological functions are still limited [9].…”
Section: Introductionmentioning
confidence: 99%
“…N = 3 (one sample for three replicates). *p < 0.05. d Transfect miR-330-3p mimics or inhibitor into synoviocytes from the control patient at different concentrations (10,20,50, and 100 nM). N = 6 (two different samples for three independent experiments).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from five TMJOA tissues and five control tissues using Trizol reagent (Invitrogen, Carlsbad, CA, USA) according to the manufacturer's protocol. The RNA concentration, purity, and integrity of each sample were quantified, and then the RNA library (mRNA and circRNA) was constructed using the methods described by Shen et al 20 . The RNA libraries were then sequenced by Cloud-seq Biotechnology (Shanghai, China).…”
Section: Rna Seqmentioning
confidence: 99%
See 1 more Smart Citation
“…The circRNAs identified in this study have not been reported previously. Therefore, we performed a literature review of circRNAs in PCa in the PubMed database, identifying 13 studies ( Xia et al, 2018 ; Shen et al, 2019 ; Song et al, 2019 ; Wang et al, 2019 ; Wu et al, 2019 ; Hu and Guo, 2020 ; Kong et al, 2020 ; Li T. et al, 2020 ; Ou et al, 2020 ; Shan et al, 2020 ; Yan et al, 2020 ; Zheng et al, 2020a , b ) of 18 circRNA–miRNA interactions. The miRNAs identified in this study have previously been shown to play important roles in PCa.…”
Section: Discussionmentioning
confidence: 99%